COVID-19 and Adult Education – a Path to Transformation of Regions in Latvia - Jekabsone, Inga (Pedagogika, 2023)
This research examines the consequences of COVID-19 on the adult education sector in Latvia in the context of regional restructuring. A survey of adult education institutions of Latvia (N = 60) was used as the main research method. Main findings of the research: in the pandemic context, the main challenges in the adult sector are related to the lack of digital skills, technological issues, and transformation of the content of the subject to distance learning.